PELATIHAN PENANGGULANGAN DAN PENCEGAHAN HIV /AIDS - Agus Mursidi; Harwanti Noviandari; Dhalia Sutopo (Khazanah Pendidikan, 2018)
HIV-AIDS in East Java is in a stage of concern with the development oftransmission. From 1989 to September 2016, PLHIV in East Java were 54,275people. Of these, those with HIV reached 36,881. While those convicted of AIDSwere 17,394 people and in 2017 reached 118,426 inhabitants. In Banyuwangi,the Banyuwangi Regency AIDS Commission, currently there are 3,260 HIVsufferers in Banyuwangi, 999 cases of AIDS sufferers, and 315 of them dead.Community service on HIV-AIDS prevention and prevention training was carriedout at the Teacher Training and Education Faculty of the PGRI BanyuwangiUniversity in October 2017. In this activity the service team trained students inovercoming and preventing HIV / AIDS. The service activity received a very goodresponse from students at PGRI Banyuwangi University.Keywords: Prevention, HIV, AIDS